Studi Perubahan Unsur Kalium Akibat Pemupukan dan Pengaruhnya terhadap Hasil Tanaman - Oviyanti Mulyani; Encep Hidayat Salim; Anni Yuniarti; Yuliati Machfud; Apong Sandrawati; Marisa Puspita Dewi (Soilrens, 2017)
Balanced fertilization is one solution to support sustainable agriculture.This experiment was conducted to determine the study of potassium caused by balanced fertilization. The experimental method used a Randomized Block Design (RBD) single factor with ten treatments and three replications, so the total is 30 experimental plots. The ten treatments consisted of : without fertilizer (0), ½, 1, 1,5 and 2 doses of organic fertilizer + without fertilizer (0), ¼, ½, ¾ and 1 doses of anorganic fertilizer. The results of this experiments showed that there were significant effects on potencial K, exchangeable K, K uptake and yield of pakchoy from combination of organic fertilizer with anorganic fertilizer. The treatment 1½ dose of organic fertilizer + 1 dose of anorganic fertilizer produce the highest yield of pakchoy with 5.13 kg plot-1 (increase 100 % than control).Keywords: Azolla pinnata compost, litter, peat, solid biofertilizer